2020
DOI: 10.1101/2020.09.09.290791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of seasonal anoxia on the microbial community structure in demosponges in a marine lake (Lough Hyne, Ireland)

Abstract: Climate change is expanding marine oxygen minimum zones (OMZs), while anthropogenic nutrient input depletes oxygen concentrations locally. The effects of deoxygenation on animals are generally detrimental; however, some sponges (Porifera) exhibit hypoxic and anoxic tolerance through currently unknown mechanisms. Sponges harbor highly specific microbiomes, which can include microbes with anaerobic capabilities. Sponge-microbe symbioses must also have persisted through multiple anoxic/hypoxic periods throughout … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 146 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Some sponges can live in anoxic conditions for several months, such as the sponges of the family Raspailidae found in the deeper cliffs of Lough Hyne (Bell & Barnes, 2000;McAllen et al, 2009;Micaroni et al, 2021). Schuster et al (2021) suggested that this tolerance could be conferred by specific bacterial symbionts, which are able to carry out anaerobic metabolism. In addition, these sponges living in anoxia are all thin crusts, with a very high surface-to-volume ratio, which could favour the exchange of gases and the release of metabolic waste (Levin et al, 1991).…”
Section: Sponge Response To Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…Some sponges can live in anoxic conditions for several months, such as the sponges of the family Raspailidae found in the deeper cliffs of Lough Hyne (Bell & Barnes, 2000;McAllen et al, 2009;Micaroni et al, 2021). Schuster et al (2021) suggested that this tolerance could be conferred by specific bacterial symbionts, which are able to carry out anaerobic metabolism. In addition, these sponges living in anoxia are all thin crusts, with a very high surface-to-volume ratio, which could favour the exchange of gases and the release of metabolic waste (Levin et al, 1991).…”
Section: Sponge Response To Hypoxiamentioning
confidence: 99%
“…Species-specific phenotypic plasticity appears to help these organisms to overcome hypoxic events, and future research will need to elucidate the mechanisms behind these changes. This exceptional adaptive capacity of sponges could be derived from their ancient evolutionary origin and could confer sponges a competitive advantage in future deoxygenated oceans over other organisms (Mills et al, 2014;Schuster et al, 2021).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Species-specific phenotypic plasticity appears to help these organisms to overcome hypoxic events, and future research will need to elucidate the mechanisms behind these changes. This exceptional adaptive capacity of sponges could derive from their ancient evolutionary origin and could confer sponges a competitive advantage in future deoxygenated oceans over other organisms (Mills et al, 2014;Schuster et al, 2021). The symbol < was used when LT50 was not reported, but more than 50% of the organisms died after a certain amount of time; while > was used when LT50 was not reached by the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis is the encrusting sponges of the family Raspailidae remaining relatively abundant in 2018. These sponges are the only ones abundant in the deeper, periodically anoxic/hypoxic areas of the lough and are better adapted to acidic, hypoxic, H2S-rich conditions (Schuster et al, 2021). While this kind of oceanographic event could occur naturally in systems like Lough Hyne, the nutrient increase recorded at Lough Hyne and the coastal areas of SW Ireland between the 1990s and 2000s could have contributed to the intensification of the anoxic/hypoxic regime as reported in many other areas of the world (Diaz and Rosenberg, 2008).…”
Section: S2mentioning
confidence: 99%
See 1 more Smart Citation